Outcomes of organ-preserving treatment of atypical hyperplasia and early stage endometrial cancer in reproductive age: A prospective and retrospective study - Lyubov T. Gadzhieva; Stanislav M. Pronin; Stanislav V. Pavlovich; Vlada V. Kometova; Levon A. Ashrafyan (IP Berlin A.V., 2023)
Aim. To evaluate the effectiveness of the intrauterine levonorgestrel-releasing device (LNG-IUD) in the treatment of atypical hyperplasia and the use of LNG-IUD in combination with a gonadotropin-releasing hormone analog (3.6 mg goserelin depot) in the treatment of stage Ia highly differentiated endometrial adenocarcinoma in women wishing to preserve childbearing function, and to assess reproductive outcomes after treatment in these women. Materials and methods. A prospective and retrospective series of cases included all patients treated with LNG-IUD or LNG-IUD combined with goserelin 3.2 for atypical hyperplasia or early endometrial cancer (EC) treated in the Department of Innovative Oncology and Gynecology of the Institute of Oncogynecology and Mammology of the Kulakov National Medical Research Center for Obstetrics, Gynecology and Perinatology from January 2018 to March 2022. Response rates and the relationship of the response with clinical and pathological factors were calculated. Results. Fifty-six patients diagnosed with atypical hyperplasia or stage Ia highly differentiated endometrial adenocarcinoma were treated with LNG-IUD and LNG-IUD combined with 3.2 mg of goserelin. Of the 56 patients who completed a 6-month course of hormonal treatment, 42 (82%) showed a complete response: 22 (91.7%) with atypical endometrial hyperplasia (AEH) and 20 (74.1%) with EC. In 4 (7.8%) patients, a partial response was reported: 2 (8.3%) with AEH and 2 (7.4%) with EC. No response was noted in 5 (9.8%) patients in the EC group only. Childbirth was reported in 13 (23.2%) women: 8 (29.6%) with AEH and 5 (17.2%) with EC. Two (3.6%) women were in the second trimester of pregnancy, and 17 (30.4%) women had an early pregnancy loss; 7 (25.9%) of them had AEH, and 10 (34.5%) had EC. The positive response rate was 90.2% at 6 months: 24 (100%) patients with atypical hyperplasia and 22 (81.5%) with EC. Patients with EC in combination with polycystic ovary syndrome and obesity and patients with the non-obese EC phenotype had a lower therapy efficacy. Conclusion. LNG-IUD therapy for the conservative treatment of atypical hyperplasia and LNG-IUD therapy combined with goserelin 3.2 for early EC led to a morphological cure in most patients and can be considered for women planning pregnancy.